2011
DOI: 10.1111/j.1440-1843.2011.01943.x
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre surveillance study on the characteristics, bacterial aetiologies and in vitro antibiotic susceptibilities in patients with acute exacerbations of chronic bronchitis

Abstract: Gram-negative bacteria including Klebsiella spp., P. aeruginosa and Acinetobacter spp. constitute a large proportion of pathogens identified in patients with AECB in some Asian countries. Surveillance on the local prevalence and antibiotic resistance of these organisms is important in guiding appropriate choice of antimicrobials in the management of AECB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
4
16
0
Order By: Relevance
“…In this study, K. pneumoniae was a common bacterial pathogen. This is similar to a previous Asian multicenter study which included Thailand 21. Our study included COPD with severe airflow limitation, which may increase lower airway bacterial colonization 22.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, K. pneumoniae was a common bacterial pathogen. This is similar to a previous Asian multicenter study which included Thailand 21. Our study included COPD with severe airflow limitation, which may increase lower airway bacterial colonization 22.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is similar to that of Narayanagowda et al 20 , Hui et al 22 and Lin et al 23 who found K. pneumoniae as the predominant organism in their study. However, they also found other gram-negative organisms like P. aeruginosa and Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 82%
“…in this study (except ampicillin and nitrofurantoin), a finding that is similar to others. 20,23 In contrast, P. aeruginosa was only >50% susceptible to cefoperazone and amikacin. Notably, the susceptibility of P. aeruginosa to imipenem was 23.8%, which is significantly lower than reported values of 74.8% in 2003 and 70.5% in 2008, in China.…”
Section: Discussionmentioning
confidence: 99%